1687. Omadacycline in Female Adults With Acute Pyelonephritis: Results from a Randomized, Double-Blind, Adaptive Phase 2 Study. (31st December 2020) - Overcash, J Scott; Tzanis, Evan; Manley, Amy; Kirsch, Courtney; Serio, Alisa W; White, Tiffany; Wright, Kelly; Chitra, Surya; Eckburg, Paul B
Abstract: Background: Omadacycline (OMC) is a novel intravenous (IV) and oral aminomethylcycline, approved in the USA for community-acquired bacterial pneumonia and acute bacterial skin and skin structure infections in adults. We present data from a randomized, adaptive dose–response phase 2 study of OMC in adult females with acute pyelonephritis (AP). Methods: Females aged ≥ 18 y with acute uncomplicated pyelonephritis were initially randomized to 1 of 4 once-daily regimens of OMC vs once-daily standard regimen of IV-to-oral levofloxacin (LEV) (total therapy: 7–10 days) (NCT03757234); the randomization algorithm was subsequently adapted by the data monitoring committee (DMC; blinded to the investigators) following interim analyses of efficacy in the microbiological-intent-to-treat (micro-ITT) population (Table 1). Efficacy was assessed for noninferiority according to investigator's assessment of clinical response (IACR) and microbiological response at post-therapy evaluation (PTE; Day 21) and end of therapy (EOT). Treatment-emergent adverse events (TEAEs) were assessed. Results were reviewed by the DMC. Table 1 Results: 201 patients were randomized. Baseline characteristics were similar across groups (Table 2 ). Among patients with an identified pathogen, the most common species was E. coli . For IACR at both EOT and PTE, no OMC group met noninferiority to LEV (Figure 1 ), as the lower limit of the 95% CI for the treatment difference exceeded −10% (range −12.4% to −34.8%). Responses at PTE were consistent with those at EOT. Microbiological responses in each OMC group were generally lower than LEV. OMC was well tolerated; 36.2% and 32.4% of OMC- and LEV-treated patients had ≥ 1 TEAE. The most frequently reported TEAEs (≥ 5%) in the OMC the LEV groups, respectively, were headache (10.2% vs 6.8%), asymptomatic bacteriuria (6.3% vs 1.4%), diarrhea (2.4% vs 6.8%), and nausea (5.5% vs 6.8%). Table 2 Figure Conclusion: In this adaptive, phase 2 study, clinical success was high for both groups, although no OMC group met criteria for noninferiority to levofloxacin in AP, potentially due to pharmacokinetic/pharmacodynamic drivers of efficacy for AP. Omadacycline was well tolerated, with a safety profile consistent with its current labeling. Further evaluation is warranted to further understand the outcomes of this study. Disclosures: J. Scott Overcash, MD, FACEP, Paratek Pharmaceuticals, Inc. (Scientific Research Study Investigator) Evan Tzanis, BS, Paratek Pharmaceuticals, Inc. (Employee, Shareholder) Amy Manley, BS, Paratek Pharmaceuticals, Inc. (Employee) Courtney Kirsch, BS, Paratek Pharmaceuticals, Inc. (Employee) Alisa W. Serio, PhD, Paratek Pharmaceuticals, Inc. (Employee, Shareholder) Tiffany White, PhD, ContraFact Corporation (Consultant, (ended Feb 2020))Facile Therapeutics (Consultant)Paratek Pharmaceuticals, Inc. (Employee) Kelly Wright, PharmD, Paratek Pharmaceuticals, Inc. (Employee, Shareholder) Surya Chitra, PhD, Paratek Pharmaceuticals, Inc. (Consultant) Paul B. Eckburg, MD, AN2 Therapeutics (Consultant)Bugworks Research (Consultant)Curza (Advisor or Review Panel member)Paratek Pharmaceuticals, Inc. (Consultant)SNIPR Biome (Consultant)Spero Therapeutics (Consultant)